Growing carrot year round is lucrative - Kalia, Pritam; Saha, Swati; Sureja, A K (Indian Horticulture, 2024)
Carrot is valued as family food because it is rich in several phytochemicals and dietary fibres. The popularity of carrots has also been influence by the introduction of technology for the year round cultivation.